Answer:
see explanation
Explanation:
Given a quadratic function in standard form ax² + bx + c : a ≠ 0
Then the axis of symmetry and the x- coordinate of the vertex, since the vertex lies on the axis of symmetry is
x = -
![(b)/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eoegn6mvxjwnsbs8qeqw3ayn0w36v7k5kl.png)
f(x) = x² + 4x + 3 ← is in standard form
with a = 1, b = 4, hence
x = -
= - 2
Equation of axis of symmetry is x = - 2
Substitute x = - 2 into f(x) for corresponding y- coordinate of vertex
f(- 2) = (- 2)² + 4(- 2) + 3 = 4 - 8 + 3 = - 1
Hence vertex = (- 2, - 1)